THE USE OF PICTURE TO IMPROVE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT SEVENTH GRADE IN SMPTK DIASPORA KABUPATEN SORONG - Ari Wibowo; Rizki Claudia Wardani H; Yanti Wattimury (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2018)
This study aimed to improve the English learning outcomes on the competence of descriptive text at seventh grade in SMPTK Diaspora Kabupaten Sorong. This study is classroom action research which, consisting of II cycles, that is cycle 1 is done for two meeting and cycle two is done for four meetings. Data retrieval is done through observation and students learning result test that is conducted at the end of each cycle. The subject of this research is seventh grade students at of academy year 2017/2018. In the cycle I there are eighteenth students have the highest score meanwhile there are five students have the lowers score. In the cycle II, there are nineteenth student have the highest score meanwhile there are four student have the lowers score, In the cycle I cycle and II there is increasing to the result of learning student.